(untitled) (Acta Scientiarum. Agronomy, 2024)
The nodulation of common beans occurs continuously until the flowering stage, followed by nodule senescence. However, reports have indicated the potential for late nodulation in this species, contributing to increased grain production. This study aimed to evaluate the occurrence of late nodulation in common beans and its contribution to plant growth. Experiments were carried out by testing two inoculation strategies: rhizobial inoculation (1) in different sections of the root system and (2) at different phenological stages. Plants were harvested at flowering and the beginning of pod filling. When the first strategy was applied, both inoculation on the seeds and throughout the pot volume resulted in greater nodulation compared to the uninoculated control. However, shoot biomass accumulation remained unaffected. When the second strategy was applied, supplementary inoculation at different stages did not improve nodulation or plant growth compared to seed inoculation. We conclude that neither method promoted effective late nodulation of common beans and that seed inoculation was sufficient to promote good vegetative development of common beans.